MEREKAYASA GENERASI PENERUS - Benny Phang Khong Wing (Studia Philosophica et Theologica, 2006)
The modern era of genetics has led people to deconstruct the classical meaning of being a human person. Genetic engineering intended to heal the genetic disease turns to be genetic enhancement. Amniocentesis confuses many women during their pregnancy and it directs them into abortions. The biomedical world leaves the prominent Hippocratic Oath, and it creates horrifying effects in the near future. Human person is not considered as a subject anymore, but an object of human productions. This article offers a response of the negative consequences of genetic engineering and amniocentesis in light of the bioethical principle of nonmaleficence, which is richly expressed in the Hippocratic Oath: primum non nocere.